Can paternal leakage maintain sexually antagonistic polymorphism in the cytoplasm?. (27th February 2015) - Kuijper, B.; Lane, N.; Pomiankowski, A.
Abstract A growing number of studies in multicellular organisms highlight low or moderate frequencies of paternal transmission of cytoplasmic organelles, including both mitochondria and chloroplasts. It is well established that strict maternal inheritance is selectively blind to cytoplasmic elements that are deleterious to males – 'mother's curse'. But it is not known how sensitive this conclusion is to slight levels of paternal cytoplasmic leakage. We assess the scope for polymorphism when individuals bear multiple cytoplasmic alleles in the presence of paternal leakage, bottlenecks and recurrent mutation. When fitness interactions among cytoplasmic elements within an individual are additive, we find that sexually antagonistic polymorphism is restricted to cases of strong selection on males. However, when fitness interactions among cytoplasmic elements are nonlinear, much more extensive polymorphism can be supported in the cytoplasm. In particular, mitochondrial mutants that have strong beneficial fitness effects in males and weak deleterious fitness effects in females when rare (i.e. 'reverse dominance') are strongly favoured under paternal leakage. We discuss how such epistasis could arise through preferential segregation of mitochondria in sex‐specific somatic tissues. Our analysis shows how paternal leakage can dampen the evolution of deleterious male effects associated with predominant maternal inheritance of cytoplasm, potentially explaining why 'mother's curse' is less pervasive than predicted by earlier work.